The impact of software quality on maintenance process - Al-Badareen, Anas Bassam; Selamat, Mohd Hasan; A. Jabar, Marzanah; Din, Jamilah; Turaev, Sherzod (North Atlantic University Union, 2011)
The software is always required to be developed and maintained a quality to the rapid progresses in industry, technology, economy, and other fields. Software maintenance is considered as one of the main issues in software development life cycle that is required efforts and resources more than other phase. Studies estimated that the cost of software maintenance rapidly increased that reached the 90% of the total cost of software development life cycle. Therefore, it is considered as an economic impact in information system community. Several researches are intended to estimate and reduce the cost of this task. This study introduces a model of software maintenance process that emphasizes the impact of the software quality on the maintenance process. The study presents the process of the software maintenance, and then discussed the quality characteristics that affect these tasks. Furthermore, the evaluation criteria for these factors are discussed.